The influence of social exclusion on adolescents' social withdrawal behavior: The moderating role of connectedness to nature. (May 2023) - Chen, Li; Zeng, Shuyu; Su, Yanxia
Abstract: If individuals do not have good peer social relationships, they will not only fail to benefit from social groups, but will have more solitary behaviors due to being excluded and rejected. And the withdrawal of choosing to be alone will induce further social exclusion. However, previous studies on social exclusion and social withdrawal have focused on children, college students, and adults, and few studies have explored adolescents as subjects. There is evidence that problematic peer relationship experiences (e.g., rejection, exclusion) are indeed a cause and consequence of social withdrawal in adolescents, and fortunately, interventions that connect people to nature may lead to many positive changes in multiple domains of functioning, such as indirect exposure to the natural environment can moderate the negative effects of an individual's exclusion. Therefore, to test the causal relationship between social exclusion and adolescent social withdrawal behavior and the effect of natural associations on adolescent social withdrawal behavior, we found through three studies that social exclusion significantly affected adolescent social withdrawal behavior, connectedness of nature, i.e., simply viewing nature pictures, significantly diminishes the effect of social exclusion on adolescents' social withdrawal behavior. Taken together, these findings underscore the importance of natural associations in influencing social withdrawal after exclusion. Highlights: Social exclusion and adolescent withdrawal behavior were positively correlated. Adolescents in the social exclusion group showed more withdrawal behaviors. Viewing nature pictures moderates the above relationship.